2016
DOI: 10.3892/mmr.2016.4947
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying mangiferin-induced apoptosis and cell cycle arrest in A549 human lung carcinoma cells

Abstract: Mangiferin, which is a C-glucosylxanthone (1,3,6,7-tetrahydroxyxanthone-C2-β-D-glucoside) purified from plant sources, has recently gained attention due to its various biological activities. The present study aimed to determine the apoptotic effects of mangiferin on A549 human lung adenocarcinoma cells. In vitro studies demonstrated that mangiferin exerted growth-inhibitory and apoptosis-inducing effects against A549 cells. In addition, mangiferin exhibited anti-tumor properties in A549 xenograft mice in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…CDK2/4/6 and cyclin D1/E are known to be involved in the regulation of G 0 /G 1 phase. Because activation of the CDK/cyclin complex initiates entry into G 1 phase, the G 0 /G 1 transition usually requires a functional CDK/cyclin complex (34). Our results indicated that quinalizarin induced A549 cell cycle arrest at G 0 /G 1 phase by suppressing CDK2/4/6 and cyclin D1/E and increasing p21 and p27 protein expression levels.…”
Section: Discussionmentioning
confidence: 62%
“…CDK2/4/6 and cyclin D1/E are known to be involved in the regulation of G 0 /G 1 phase. Because activation of the CDK/cyclin complex initiates entry into G 1 phase, the G 0 /G 1 transition usually requires a functional CDK/cyclin complex (34). Our results indicated that quinalizarin induced A549 cell cycle arrest at G 0 /G 1 phase by suppressing CDK2/4/6 and cyclin D1/E and increasing p21 and p27 protein expression levels.…”
Section: Discussionmentioning
confidence: 62%
“…In terms of antineoplastic mechanisms, mangiferin has been shown to act on multiple molecular targets, which mediate the underlying biological signaling processes that inhibit the initiation, promotion, and metastasis of cancer [14][15][16][17][18][19][20]. For lung cancer, studies have found that decreased activities of some biochemical pathways in lung cancer-bearing animals were prevented after pre-and posttreatment with mangiferin and even approached normal control animal values [21][22][23][24][25]. It was also shown that the anticancer effect of mangiferin was more pronounced when used as a chemopreventive agent, rather than as a chemotherapeutic agent, against B(a)P-induced lung carcinogenesis [26].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the anticancer effect of mangiferin was more pronounced when used as a chemopreventive agent, rather than as a chemotherapeutic agent, against B(a)P-induced lung carcinogenesis [26]. In addition, mangiferin was able to decrease the tumor mass by helping the cisplatin with antiproliferative effects on A549 cells [25]. According to recent ndings by Grauzdytė D et al, mangiferin ameliorates oxidative stress, accelerates the wound healing process and restores the proliferation rate in polycyclic aromatic hydrocarbon-exposed bronchial epithelium [27].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for lung cancer is unfavorable, and novel therapeutic strategies to improve the outcome of patients with NSCLC are required. Traditional Chinese medicine is a source of novel compounds with antineoplastic activity, including isocryptotanshinone, mangiferin and xanthatin (4)(5)(6). Tetrahydrocurcumin (THC) is a traditional Chinese medicine isolated from Curcuma wenyujin (Chen & Ling, 1981).…”
Section: Introductionmentioning
confidence: 99%